(untitled) (Mustansiria Dental Journal, 2004)
Abstract: The objective of this research was to investigate the resin -dentin interface of the Excite bonding system applied to wet and dry dentin by using scanning electron microscope. The adhesive and the composite were applied according ot the manufacturer instruction to a standardized buccal and palatal class V cavities prepared on human upper first premolar. The teeth were sectioned vertically ot examine the resin dentin interface, several morphological differences were seen between wet and dry technique, the hybrid layer analysis revealed different hybridization patterns, suggesting that the attachment seems ot be influenced by many factors and a standardization of dentinal substrate si impossible.